1966
DOI: 10.1002/pol.1966.150040720
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of syndiotactic polypropylene

Abstract: The preparation and characterization of syndiotactic polypropylene are reported. The influence of polymerization variables on the syndiotactic regulating capacity of the VCl4–AlEt2Cl catalyst were investigated. Vanadates could be substituted for VCl4, and Al(C6H5)2Cl or AlEt2Br for AlEt2Cl under suitable conditions. Hydrogen functioned as a chain transfer agent for the AlEt2Cl–VCl4 catalyst, and polymerizations which were terminated with tritiated alcohols yielded polymers containing bound tritium. The syndio‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

1971
1971
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 13 publications
1
49
0
2
Order By: Relevance
“…Boor and Youngman attributed these two peaks to the helical form and the planar zigzag form, respectively. 17 Marchettis believed that the two peaks are respectively produced by the fusion of a crystal incorporated with stereodefects and a relatively perfect crystal. 10 Lovinger et al suggested that the lower peak may be due to lower molecular weight materials rejected during crystallization.…”
Section: Melting Behavior Of S-pp Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boor and Youngman attributed these two peaks to the helical form and the planar zigzag form, respectively. 17 Marchettis believed that the two peaks are respectively produced by the fusion of a crystal incorporated with stereodefects and a relatively perfect crystal. 10 Lovinger et al suggested that the lower peak may be due to lower molecular weight materials rejected during crystallization.…”
Section: Melting Behavior Of S-pp Fractionsmentioning
confidence: 99%
“…Multiple melting peak phenomena were observed by many authors. 5,11,17,18 There are still controversies about the origination of the double melting peak. Boor and Youngman attributed these two peaks to the helical form and the planar zigzag form, respectively.…”
Section: Melting Behavior Of S-pp Fractionsmentioning
confidence: 99%
“…Die Fraktionierung von Nr. 16 wurde nicht versucht, da alle Versuche [10][11][12] zur Fraktionierung von syndiotaktischem Polypropylen bisher mialungen sind. …”
Section: Fraktionierungenunclassified
“…Wird die Bruckenbindung wieder geoffnet und verbleibt dabei eine Athylgruppe am Metallzentrum, dann spaltet die sehr instabile Cr(ii1)-Kohlenstoff-Bindung auf und gibt eine Cr(II)-Spezies (6), die wahrscheinlich durch den Phosphit-Liganden L stabilisiert wird (in Abwesenheit von Phosphit entsteht ein Niederschlag). Z(acac),Cr(~~i)C,H, -Z(acac),Cr(n)L, + C2H, + C2H, (6) Weiterer Austausch der acac-Liganden durch C1 oder C,H, kann dann zu einer ahnlichen Spezies (7) fuhren, wie sie bereits oben fur Vanadium formuliert wurde, vielleicht ebenfalls im Gleichgewicht mit einem Komplex rnit zwei Bruckenbindungen Die Gelpermeationschromatogramme geben einige zusatz-liche Informationen uber diesen Punkt. In den Systemen rnit (C,H,),AlCl (Abb.…”
Section: Gegenwartiger Standunclassified